Digitalization of Herbarium Collections: A Plant Identification Research for the Botanical E-Encyclopedia - Ummi Hiras Habisukan; Weni Lestari (Universitas Nusantara PGRI Kediri, 2026)
Biology learning, particularly on the topic of Plantae, often poses difficulties for students due to the complexity of scientific terminology, morphological diversity, and the limited use of innovative learning media, which are still predominantly based on textbooks and static images. This condition calls for innovative media that not only present information accurately but also provide a more interactive learning experience aligned with the characteristics of the digital generation. This study aims to develop an E-Encyclopedia based on herbarium collections as a learning medium for biology in the Plantae topic while supporting the digitalization of botanical knowledge. The research employed the 4D development model (Define, Design, Develop, Disseminate). The subjects of the study included teachers and students at SMA PGRI 1 Palembang. The results of the define stage revealed the lack of innovative media and the difficulty students faced in understanding Plantae concepts. The design stage produced a prototype of an E-Encyclopedia based on herbarium documentation featuring interactive elements and plant specimen visualization. Validation results from material, media, and language experts indicated a very valid category with an average expert validation score of 91.9%. The practicality test through teacher responses achieved 91.4% (very good category), while student responses reached an average of 93,3% (very good category). The effectiveness test using pretest and posttest data from 38 students showed an improvement in learning outcomes, with an average pretest score of 55 and a posttest score of 82, resulting in an N-Gain of 0.56 (moderate category) and a significant t-test result (p < 0.05), confirming the media’s effectiveness. These results indicate that the herbarium-based E-Encyclopedia developed not only enriches digital learning resources but is also proven to be valid, practical, and effective in improving biology learning outcomes, especially on the Plantae topic. Moreover, this product supports the conservation of botanical knowledge, facilitates access to plant biodiversity data, and enhances scientific literacy in the digital era.